Foliar applications of calcium do not impact on fruit and leaf nutrient concentration or quality of 'O'Neal' blueberry. Issue 5 (3rd September 2019) - Manzi, Matías; Lado, Joanna
ABSTRACT: Calcium (Ca) has been considered a key element in maintaining fruit quality and extending the storage period of several fruits. The main blueberry (interspecific hybrids of Vaccinium corymbosum x V. darrowii ) market for the Southern Hemisphere production involves a long transport between harvest and consumption. Foliar Ca sprays during the pre-harvest constitutes a common practice for improving Ca concentration [Ca] in fruits and therefore in alleviating the loss of firmness, dehydration and rot decay during postharvest. In this study, two formulations of Ca; Ca-nitrate [Ca(NO3 )2 ] and chelate Ca-oxide (Ca-gluconate; Ca-Glu) were sprayed four times during pre-harvest of blueberry cv. O'Neal. [Ca] in the fruits was followed after each application and fruit quality parameters were determined at harvest and during 28 days of cold storage. Both formulations were ineffective in increasing [Ca] in the berries (or leaves) after any of the four applications. In fruits, [Ca] decreased from 0.32% at 25 days after full bloom (DAFB) to 0.11% Ca at harvest time. Other minerals such as magnesium (Mg), potassium (K), or nitrogen (N) remained unaffected by the treatments. Data shows that foliar pre-harvest applications of Ca, regardless of formula, were ineffective at increasing [Ca] or improving the quality of the fruit.